Teological overview Choan-Seng Song about Jesus suffering - Suksmono, Ari; Ming, David (Eximia, 2023)
Choan-Seng Song is an Asian theologian who is quite determined to think about how to apply biblical values in an Asian context. Song tried to theologize not based on Western theology but instead he formulated Asian theology, which took the area not only in the church but more broadly in Asian society. Shoki Coe, a theologian from Taiwan - together with Song - who is also Director of the Theological Education Fund, wrote in the introduction to Song’s book titled Christian Mission in Reconstruction: An Asian Analysis: First, Song’s challenge to theologize in an Asian context is very heavy and Song with enthusiasm who overflowed trying to answer it. Second, Song reflects his theology well and consistently. Song corrected the mission of Western Christians who had lost the dynamics of the incarnation. His theological strength was to reject Western values and Song found God’s incarnation in the lives of Asians. The author uses the approach of exegesis research methods and apologetics to examine the extent to which the concept of Jesus - which is central to Song’s theology - as a figure of "suffering" is applied to the phenomena that occur in society. The essence of the contextual pressures is how Song used to break through the values of the suffering Jesus. The purpose of this writing is divided into three parts, namely: the first part contains the concept of Song about Jesus suffering, which is seen from the biblical aspect, the symbol of the cross, Jesus as the center of the mission of suffering in the world, theology of the people, the suffering messiah, and the politics of the cross. The second part, to look for the biblical basis of Jesus who suffered (for aesthetics), the author executes Mk 8:31; 9:31; and 10: 33-34 and to find the biblical basis Suffering is a characteristic of Christians, the writer executes 1Pet 4: 12-19. The third part is evaluating (apologetics) Song’s thoughts with the author’s exegesis from positive and negative aspects.